Z korespondencji sławnych jezuitów. Piotr Skarga do Hieronima Nadala - Mrozek-Kochanek, Kamila (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
This essay reminds us of the correspondence between Piotr Skarga and Jerome Nadal. The author discusses all seven letters of their written dialogue. T hey exchanged not so many letters and we cannot tell enough about Nadal’s personality and his relationship with a well-known Polish preacher, but their correspondence is really interesting as a unique source of knowledge about the early Society of Jesus, history of the Catholic Church and customs in old Poland, which are described from the point of view of Jesuits.